2014
DOI: 10.1089/thy.2013.0614
|View full text |Cite
|
Sign up to set email alerts
|

Apigenin in Combination with Akt Inhibition Significantly Enhances Thyrotropin-Stimulated Radioiodide Accumulation in Thyroid Cells

Abstract: Taken together, Apigenin may serve as a dietary supplement in combination with Akt inhibitors to enhance therapeutic efficacy of radioiodine for thyroid cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…Treatment with apigenin increases radioiodide accumulation in thyroid cells expressing BRAFV600E and in primary cultured thyroid tumor cells from TRβ (PV/PV) mice. Thus, along with Akt inhibitors, apigenin can further enhance the efficacy of radioiodine therapy for thyroid cancer patients [195]. Apigenin-induced cell death has been shown to involve autophagy in papillary thyroid cancer, perhaps because of ROS stimulation, induction of DNA damage and G2/M phase cell cycle arrest [196].…”
Section: 0 Effect Of Apigenin In Various Human Cancersmentioning
confidence: 99%
“…Treatment with apigenin increases radioiodide accumulation in thyroid cells expressing BRAFV600E and in primary cultured thyroid tumor cells from TRβ (PV/PV) mice. Thus, along with Akt inhibitors, apigenin can further enhance the efficacy of radioiodine therapy for thyroid cancer patients [195]. Apigenin-induced cell death has been shown to involve autophagy in papillary thyroid cancer, perhaps because of ROS stimulation, induction of DNA damage and G2/M phase cell cycle arrest [196].…”
Section: 0 Effect Of Apigenin In Various Human Cancersmentioning
confidence: 99%
“…Treatment with apigenin at concentrations of 12.5∼100 μM can inhibit the proliferation of BCPAP cells arrested in the G2/M phase and induce autophagy via ROSmediated DNA damage [39]. Moreover, combining with apigenin and AKT inhibitors enhances the antitumor effects of radioiodine in both BRAF V600E -expressed rat thyroid cells and primary cultured PTC cells from TRβ PV/PV mice [40]. Unlike those of apigenin, the effects of quercetin on thyroid cells have been disputed.…”
Section: Flavonoidsmentioning
confidence: 99%
“…NIS protein level was decreased by 43 % upon 12-h treatment of TGF-β in PCCl3 thyroid cells under chronic TSH stimulation, where the half-life of NIS protein is 5 days in the absence of TGF-β (Lakshmanan and Jhiang, unpublished data). We reported that Akt inhibitor alone [33] or in combination with apigenin [45] increased iodide influx rate without increasing cell surface NIS protein levels.…”
Section: Modulation Of Nis-mediated Iodide Influx Iodide Efflux Andmentioning
confidence: 99%
“…Ser-43 was conserved in human NIS, and its phosphorylation is also critical for hNIS activity. Interestingly, we noted that NIS mobility was shifted upwards in SDS-denatured polyacryl-amide gel electrophoresis upon combination treatment of Akt inhibitor and apigenin in PCCl3 rat thyroid cells [45]. The nature of this mobility shift in NIS remains unclear and it may be due to a post-translational modification.…”
Section: Modulation Of Nis-mediated Iodide Influx Iodide Efflux Andmentioning
confidence: 99%